Catholicism and democracy: a reconsideration - Bell, Edward (The journal of religion & society, 2008)
An established approach to the emergence and consolidation of secular democracy maintains that democracy requires a supportive culture, and that certain national and religious cultures are better suited to democracy than others. Catholicism (especially pre-Vatican II Catholicism) is typically portrayed by scholars in this school as being inimical to democracy. The rational choice perspective, by contrast, posits that interests, resources, and strategic power relationships drive the democratization process, and that culture is largely irrelevant. This paper examines the historical relationship between the Catholic Church and secular democratic institutions and concludes that the rational choice model offers more insight into that relationship than the cultural model. Specifically, the notion that Catholicism was an impediment to democratization is shown to be problematic.